Population interactions between aphids and their natural enemies in cotton, in two Tolima zones - VERGARA-RUIZ, RODRIGO; GALEANO-O., PEDRO EDGAR (Revista Colombiana de Entomología, 1994)
Understanding the interactions of phytophagous insects with their natural enemies is a fundamental basis to elaborate cherries for insect population management. Aphids in the cotton crop may constitute a problem or serve as a natural diet for the establishment of parasitoids and predator insects. To study the interactions between aphids and their natural enemies, weekly visits were carried out in commercial plots of cotton crops located in Armero and Espinal (Tol.) corresponding to areas that are part of the tropical dry forest. These visits were done from a week before planting, during the crop' s life cycle until the harvest time and even at ratoon time. This work was realized in 1991A by taking 20 sites per hectare and in each of them, two léaves at random from the upper third of the evaluated plants. Predators were counted visually. Parasitoids, pathogens, and aphids from each sample were quantified in the laboratory. Values of the climatic parameters were established in each visit to make a regression analysis. Aphids' spatial distribution was also calculated as well as their economic threshold. The results demostrated that Aphis gossypii Glover (Homoptera: Aphididae) and the benefic species Coleomegilla maculata DeGeer, Cycloneda sanguinea (L.) andScymnus sp. (Coleoptera: Coccinellidae); Chrysopa sp. (Neuroptera: Chrysopidae) yLysiphlebus testaceipes (Cresson) (Hymenoptera: Braconidae) were predominant. When they act together, the climatic parameters make the interaction work but if there is an independent action its effect alternate from positive to negative. Aphids' spatial distribution is in groups or aggregates and injury levels were reached only in 10% of the evaluations.